Thymus algeriensis Bioss & Reut: Relationship of phenolic compounds composition with in vitro/in vivo antioxidant and antibacterial activity. (October 2020) - Righi, Nadjat; Boumerfeg, Sabah; Fernandes, Pedro A.R.; Deghima, Amirouche; Baali, Faiza; Coelho, Elisabete; Cardoso, Susana M.; Coimbra, Manuel A.; Baghiani, Abderrahmane
Graphical abstract: Highlights: Phenolic compounds were extracted and purified from Thymus algeriensis . T. algeriensis showed in vitro and in vivo antioxidant effects. T. algeriensis purified extracts presented antibacterial effect against 5 bacterial strains. Antibacterial properties were attributed to rosmarinic acid, kaempferol and eriodictyol derivatives. Abstract: Thymus algeriensis Bioss & Reut is an Algerian native plant traditionally used for culinary and medicinal purposes. To evaluate the in vivo antioxidant and antimicrobial properties of T. algeriensis, phenolic compounds were extracted using hydromethanolic solutions and administrated to Swiss albinos mice. It was observed that the plasma antioxidant capacity increased, as well as catalase and glutathione levels, whereas malondialdehyde decreased. In vitro assays confirmed that the extract scavenged 2, 2-diphenyl-1-picrylhydrazyl, DPPH (7 µg/mL), chelated (EC50 : 512 µg/mL) and reduced iron ions (5.3 mM FeSO4 /g), and inhibited β-carotene bleaching (90% at 2 mg/mL). Antibacterial effects were also observed towards Salmonella typhimurium and Proteus mirabilis . However, the methanolic fraction obtained by reversed solid phase cartridge, showed antibacterial activity against Escherichia coli (MIC = 9.37 mg/mL), Proteus mirabilis (MIC = 4.68 mg/mL), Salmonella typhimurium (MIC = 7.06 mg/mL), Micrococcus luteus (MIC = 7.03 mg/mL), and Bacillus cereus (MIC = 2.34 mg/mL) . UHPLC-DAD-ESI-MS n analysis showed that these properties could result from rosmarinic acid, caffeoyl rosmaniric acid, and kaempferol and eriodictyol glycoside derivatives. These results pave the way for the understanding of T. algeriensis traditional applications and its use for the development of novel food applications.